Cost-utility analysis of Coronary Artery Calcium screening to guide statin prescription among intermediate-risk patients in Thailand - Pakpoom Wongyikul; Phichayut Phinyo; Pannipa Suwannasom; Apichat Tantraworasin; Surasak Saokaew (PLoS ONE, 2025)
Objective This study aims to evaluate the cost-utility of Coronary Artery Calcium (CAC) screening for primary prevention in Thai patients with intermediate cardiovascular disease (CVD) risk, compared to the current practice according to the ACC/AHA 2019 guideline recommendation without the use of a CAC score. Methods A hybrid model combining a decision tree and a Markov model was constructed to compare costs and QALYs from a societal perspective. The model evaluated a target population of statin-naïve individuals aged 40–75 with intermediate CVD risk. We assessed the impact of statin initiation for primary prevention based on the ACC/AHA 2019 guideline with CAC screening compared to without CAC screening over a 35-year time horizon. The service costs and related household expenses were based on the Thai setting. The incremental cost-effectiveness ratio (ICER) was compared against the official willingness-to-pay threshold of Thailand (160,000 THB, approximately 4,400 USD per QALY). Probabilistic and additional one-way sensitivity analyses were performed to assess the robustness of the model and evaluate how variations in key assumptions impact the results. These analyses help determine the reliability of the findings by exploring the extent to which changes in input parameters influence the overall conclusions. Results The CAC screening strategy required an incremental cost of 10,091 THB to gain 0.62 QALYs per person, resulting in an ICER of 16,308 THB per QALY gained. For the probabilistic sensitivity analysis, at the official Thai threshold, the probability of cost-effectiveness was 71% for CAC screening. Sensitivity analyses based on varying the effect of drug adherence, drug cost, incidence of CVD events, and the distribution of CAC scores demonstrated robust cost-effectiveness favouring CAC screening. Conclusion CAC screening strategy is cost-effective in the Thai context, especially when the cost of screening and high-potency statins is low.